Can Online Consumers Contribute to Drug Knowledge? A Mixed-Methods Comparison of Consumer-Generated and Professionally Controlled Psychotropic Medication Information on the Internet - Hughes, Shannon; Cohen, David (JMIR Publications, 2011)
BackgroundOngoing initiatives to filter online health searches exclude consumer-generated content from search returns, though its inferiority compared with professionally controlled content is not demonstrated. The antidepressant escitalopram and the antipsychotic quetiapine have ranked over the last 5 years as top-selling agents in their respective drug classes. Both drugs have various off-label mental health and non-mental health uses, ranging from the relief of insomnia and migraines to the treatment of severe developmental disorders. ObjectiveOur objective was to describe the most frequently reported effects of escitalopram and quetiapine in online consumer reviews, to compare them with effects described in professionally controlled commercial health websites, and to gauge the usability of online consumer medication reviews. MethodsA stratified simple random sample of 960 consumer reviews was selected from all 6998 consumer reviews of the two drugs in 2 consumer-generated (www.askapatient.com and www.crazymeds.us) and 2 professionally controlled (www.webmd.com and www.revolutionhealth.com) health websites. Professional medication descriptions included all standard information on the medications from the latter 2 websites. All textual data were inductively coded for medication effects, and intercoder agreement was assessed. Chi-square was used to test for associations between consumer-reported effects and website origination. ResultsConsumers taking either escitalopram (n = 480) or quetiapine (n = 480) most frequently reported symptom improvement (30.4% or 146/480, 24.8% or 119/480) or symptom worsening (15.8% or 76/480, 10.2% or 49/480), changes in sleep (36% or 173/480, 60.6% or 291/480) and changes in weight and appetite (22.5% or 108/480, 30.8% or 148/480). More consumers posting reviews on consumer-generated rather than professionally controlled websites reported symptom worsening on quetiapine (17.3% or 38/220 versus 5% or 11/220, P < .001), while more consumers posting on professionally controlled websites reported symptom improvement (32.7% or 72/220 versus 21.4% or 47/220, P = .008). Professional descriptions more frequently listed physical adverse effects and warnings about suicidal ideation while consumer reviews emphasized effects disrupting daily routines and provided richer descriptions of effects in context. The most recent 20 consumer reviews on each drug from each website (n = 80) were comparable to the full sample of reviews in the frequency of commonly reported effects. ConclusionConsumer reviews and professional medication descriptions generally reported similar effects of two psychotropic medications but differed in their descriptions and in frequency of reporting. Professional medication descriptions offer the advantage of a concise yet comprehensive listing of drug effects, while consumer reviews offer greater context and situational examples of how effects may manifest in various combinations and to varying degrees. The dispersion of consumer reviews across websites limits their integration, but a brief browsing strategy on the two target medications nonetheless retrieved representative consumer content. Current strategies for filtering online health searches to return only trusted or approved websites may inappropriately address the challenge to identify quality health sources on the Internet because such strategies unduly limit access to an entire complementary source for health information.